Whither the Philippines in the 21st century? - Severino, Rodolfo C.; Salazar, Lorraine Carlos (Konrad Adenauer Stiftung Institute of Southeast Asian Studies, 2007)
Philippine observers are often baffled by the economic and political turmoil that dominates headlines about the country. Yet, at the same time, the Philippines continues to hold the potential for successfully combining political freedoms with sustained economic growth and, thus, improving the lives of its people. In this book, a team of distinguished scholars examines these seemingly contradictory trends in order to gain a sense of the country's prospects. Reassessing the fascinating and puzzling "Philippines conundrum" from various angles, the analyses contribute sharp and fresh insights into a variety of areas including: the presidency and political parties; constitutional change and federalism; the roles of the military, religion, and the media in politics; the conflict in Mindanao; the communist insurgency; macroeconomic developments, issues, and trends; the investment climate and business opportunities; poverty, unemployment, and income inequality; migration and remittances; and the Philippine development record in comparative perspective. While the analyses offered in this volume do not arrive at a consensus, they provide a deeper perspective and a more balanced appreciation of events in the country and a glimpse of the prospects and challenges that it faces. -- Publisher's Description.